The Intelligent Trainer: What Simulation Training Uses AI? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into simulation training is rapidly transforming professional education across high-stakes industries, from hea...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning